Brassinolide Increases Potato Root Growth In Vitro in a Dose-Dependent Way and Alleviates Salinity Stress. (10th October 2016) - Hu, Yueqing; Xia, Shitou; Su, Yi; Wang, Huiqun; Luo, Weigui; Su, Shengying; Xiao, Langtao
Abstract : Brassinosteroids (BRs) are steroidal phytohormones that regulate various physiological processes, such as root development and stress tolerance. In the present study, we showed that brassinolide (BL) affects potato root in vitro growth in a dose-dependent manner. Low BL concentrations (0.1 and 0.01 μ g/L) promoted root elongation and lateral root development, whereas high BL concentrations (1–100 μ g/L) inhibited root elongation. There was a significant (P < 0.05 ) positive correlation between root activity and BL concentrations within a range from 0.01 to 100 μ g/L, with the peak activity of 8.238 mg TTC·g −1 FW·h −1 at a BL concentration of 100 μ g/L. Furthermore, plants treated with 50 μ g/L BL showed enhanced salt stress tolerance through in vitro growth. Under this scenario, BL treatment enhanced the proline content and antioxidant enzymes' (superoxide dismutase, peroxidase, and catalase) activity and reduced malondialdehyde content in potato shoots. Application of BL maintain K + and Na + homeostasis by improving tissue K + /Na + ratio. Therefore, we suggested that the effects of BL on root development from stem fragments explants as well as on primary root development are dose-dependent and that BL application alleviates salt stress on potato by improving root activity, root/shoot ratio, and antioxidative capacity in shoots and maintaining K + /Na + homeostasis in potato shoots and roots.